Childbirth Self-Efficacy and Childbirth Expectation of Adolescent Mothers in Indonesia. (29th March 2019) - Rahmawati, Veronica Yeni; Rachmawati, Imami Nur; Budiati, Tri
ABSTRACT: To identify a correlation between childbirth self efficacy and childbirth expectation of adolescent mothers in Indonesia, this cross-sectional study applied consecutive sampling. The sample was 135 adolescent mothers. Instruments utilized were structured questionnaire, including a demographic questionnaire, Child Birth Self-Efficacy Inventory (CBSEI), Childbirth Expectation Questionnaire (CEQ), Marital Adjustment Test (MAT), and London Measure of Unplanned Pregnancy (LMUP). All questionnaires were in Indonesian versions. The correlation of childbirth self-efficacy and childbirth expectation was analyzed using chi-square. Most adolescent mothers had low childbirth self-effication (63.7%). The results showed a significant correlation between childbirth self-efficacy and childbirth expectation of adolescent mothers ( p = 0.003, OR 2.8, 95% CI 1.126 to 8.544). These results show that special assistance for adolescent mothers in facing childbirth is necessary to improve self-efficacy.